Development and validation of stability indicating LC-MS/MS Technique for the quantification of tapentadol in biological matrices: Application to bioavailability study in healthy rabbits - Phanindra Adluri, Yamsani Shravan Kumar (Journal of Applied Pharmaceutical Science, 2019)
An Liquid chromatography tandem mass spectrometry (LC-MS/MS) technique is one of the best analytical methods for the quantification of drugs in biological samples. A stability-indicating analytical technique was developed for the quantitation of tapentadol in biological matrices as tapentadol with short runtime. Developed technique also suitable for bioavailability studies in healthy rabbits. Separation of tapentadol and tapentadol-d3 were achieved from plasma sample with solid-phase extraction and elution was processed with Luna-C18 (5 μ, 100 mm × 4.6 mm) stationary column with movable phase ratio comprising 2-mM ammonium acetate buffer (pH-3.6) and acetonitrile in the proportion of 10:90 % V/V. Quantitation was processed by processing the transitions of tapentadol and tapentadol-d3 at m/z 222.2 → 177.1 and 228.2 → 183.1, respectively, in positive ionization mode. Linearity was performed over the concentration range of 0.121 to 35.637 mg/ml (R2 > 0.99) without matrix effect (2.74%). The inter- and intra-day precision findings were within 8.62% and 11.38%, respectively. Stability data showed that the tapentadol was stable when it exposed to different stability conditions. This technique was effectively applied to bioavailability studies of tapentadol in healthy rabbits.
Keywords: Tapentadol, LC-MS/ MS, validation, matrix effect, healthy rabbits and bioavailability study.